Pemanfaatan Potensi Desa di Desa Ngawis, Kecamatan Karangmojo, Kabupaten Gunung Kidul, Provinsi DIY - Pratama, Yohanes Mario (Jurnal Atma Inovasia, 2022)
Ngawis Village is a village located in Karangmojo District, Gunungkidul Regency, DIY, which has potentials in the field of natural resources that can be developed. The village potentials in Ngawis Village are found in the chili, onion and coconut cultivation in the village. The results of chili, onion and coconut cultivation can be developed into processed products from Ngawis Village. The purpose of the products of Ngawis Village is to increase Ngawis Village’s income and introduce Ngawis Village more widely to Indonesia. In utilizing the village potentials, a pocket book is made to make it easier for the villagers to understand how to develop the village potential that are owned by Ngawis Village.